KEBIJAKAN MERDEKA BELAJAR DI PENDIDIKAN DASAR: RESPONS GURU DAN IMPLIKASI BAGI PEMBELAJARAN - Hasanah, Uswatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Merdeka Belajar is a policy aimed at facilitating teachers in implementing online learning during the pandemic. This policy seeks to realize the essence of education, where students are granted the freedom to learn and to develop their competencies. The success of the Merdeka Belajar policy depends greatly on the roles of principals and teachers, as key actors in school-based education. When Merdeka Belajar is fully embraced by teachers, it will also be reflected in students. This study aims to explore teachers' responses to the Merdeka Belajar Kampus Merdeka policy. A descriptive quantitative method was used in this research, with a questionnaire distributed via Google Forms as the primary instrument. The respondents included 47 teachers from 11 primary-level schools. The data obtained were analyzed using single-tabulation and percentage techniques. The results of this study indicate that teachers understand the concept of Merdeka Belajar, agree with its implementation implications in schools, and believe that Merdeka Belajar-based teaching and assessment will enhance students' literacy and numeracy skills.